1998
DOI: 10.1093/jac/41.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of staphylococci in The Netherlands: surveillance by an electronic network during 1989-1995

Abstract: An electronic surveillance network for monitoring antibiotic resistance in The Netherlands has been in operation since 1989. Seven public health laboratories participate and the system covers about 25% of all bacteriological determinations in The Netherlands. This paper reports the results of staphylococci isolated in the period 1989-1995. About 0.3% of the Staphylococcus aureus isolates in the study period were resistant to methicillin. This low percentage may be due to the restrictive use of antibiotics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 23 publications
2
53
1
Order By: Relevance
“…Colonies suspect of being MRSA were tested by PCR for the S. aureus specific DNA fragment (Martineau et al, 1998), the mecA gene (De Neeling et al, 1998), and the Panton-Valentine leucocidin toxin genes (Lina et al, 1999).…”
Section: Identification Of Bacteriamentioning
confidence: 99%
“…Colonies suspect of being MRSA were tested by PCR for the S. aureus specific DNA fragment (Martineau et al, 1998), the mecA gene (De Neeling et al, 1998), and the Panton-Valentine leucocidin toxin genes (Lina et al, 1999).…”
Section: Identification Of Bacteriamentioning
confidence: 99%
“…All MRSA isolates were genetically characterized by PCR specific for S. aureus [22], the mecA gene [23], and the Panton-Valentine leucocidin (PVL) toxin genes [24]. Staphylococcal protein A (spa) typing was conducted according to Harmsen et al [25].…”
Section: Microbiological Examinationmentioning
confidence: 99%
“…An Etest (AB Biodisk, Solna, Sweden) showed that the oxacillin MIC for the isolates of the dog and the family members was 192 mg/liter. The presence of the mecA gene was demonstrated by a positive mecA PCR for all isolates, as previously described (2). PFGE was carried out as described by Schwarzkopf et al (12).…”
Section: Case Reportmentioning
confidence: 99%